WOMEN IN MEDIEVAL INDIA - Venkatesh .R; Mr.M.Gopi (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2021)
This research paper aims to explore the lives and status of women in medieval India. The paper discusses the social, economic, and political conditions of women during the period, including their access to education, property rights, and participation in public life. The study draws upon a range of primary and secondary sources, including historical documents, literary works, and archaeological findings, to present a comprehensive understanding of the status of women in medieval India. The paper concludes by discussing the changes that occurred in the status of women over time and the factors that influenced these changes.